4CPS-246 Impact of medication review to optimise prescriptions of nursing home residents. (2nd March 2018) - Cabrit, L; Pagès, A; Rouch, L; Magre, E; Jullien, A; Gawel, E; Raynal, A; Pluye, M; McCambridge, C; Cestac, P; Mazières, C Laffon de
Abstract : Background: In our hospital, a day care centre is dedicated to dependent elderly patients living in nursing homes to explore their general health status, specific problems and to optimise their medical care. Medication review is performed daily by both clinical pharmacists and geriatric physicians. This review aims to identify potentially inappropriate drug prescribing (PIDP) according to explicit and implicit criteria, and then to propose optimisations to general practitioners (GP). Purpose: The main objective was to assess the impact of medication review on GP's drug prescriptions' optimisation after a 6 month period. Material and methods: A monocentric study of drug optimisation proposals was performed from 1 January to 31 2017 in the day care centre. Explicit criteria were based on the Summary of Product Characteristics, on the European list of potentially inappropriate medications (EU-PIM), 1 on the START and STOPP criteria 2 and the guidelines of the French Health Agencies. Implicit criteria were based on patients' clinical and biological data. The rate of acceptance was determined after interviewing nursing home staff and GPs. Results: Among the 54 patients included, the mean age was 85.8 years and 76% were females. Patients had an average of 8.47 drugs. Polypharmacy (more than five drugs) was found in 83% of patients. 3.8 optimisation proposals per patient were done in medical letters. Seventy-three per cent were potentially inappropriate drugs identified, considering explicit criteria. Proposals were related to untreated indications (32% of the patients), and to drugs prescribed without any indication (23%). The majority of proposals involved vitamins D or B9 (23%), proton pomp inhibitors (7%) and benzodiazepines (5%). The median acceptance rate by GPS was 51%. Conclusion: Our work suggests that numerous patients have a PIDP and that such a situation could be optimised by a close collaboration between clinical pharmacists and physicians. Patients' hospitalisation in day care centres appears to be an efficient system of improving prescriptions of dependent elderly patients in nursing homes. References and/or Acknowledgements: 1. Renom-Guiteras A, et al. The EU(7)-PIM list. Eur J Clin Pharmacol2015;71:861–75. 2. O'Mahony D, et al. STOPP/START criteria for potentially inappropriate prescribing in older people: Version 2. Age Ageing2015;44:213–8. No conflict of interest